WEB SERVICE PADA APLIKASI SMART CAMPUS UNISBANK BERBASIS ANDROID - Zuliarso, Eri; Wibowo, Sayogo (Information Technology and Telematics, 2018)
ABSTRACT Stikubank University is one of the universities in the city of Semarang. With the rapid technological advances, the campus information system, which was originally developed by the author, became an Android-based Smart Campus application. Data collection methods used are methods of observation, interviews and literature studies. The system development methodology in this study uses the Waterfall methodology. The results in this study are the creation of a smart campus application that is based on android, and in its research management using the AngularJS Framework and the Cordova Framework by using web service technology, the android application can easily obtain student data and can be utilized for the convenience of accessing information.